Ultrasonic-assisted rapid extraction of cassia sieberiana D.C.: a box-behnken design process optimisation - Jibril Saidu (Tanjung Malim, 2021)
Ultrasonic-assisted rapid extraction of cassia sieberiana D.C.: a box-behnken design process optimisation by Jibril Saidu